IMPLEMENTASI SISTEM PENANAMAN LORONG (ALLEY CROPPING) RUMPUT GAJAH DENGAN INDIGOFERA TERHADAP PENINGKATAN PRODUKSI DAN KUALITAS SUSU SAPI FRIESIAN HOLSTEIN - Ako, A.; Utamy, R.F.; Hasbi, H.; Hatta, M.; Maruddin, F.; Churriyah, A.N.; Rahman, A.A. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana Mengabdi, 2023)
Sipatuo Farmers Group is the Dairy Cow Farmer Group in Enrekang Regency, South Sulawesi. Their main income is Dangke, which is a local cheese. Dangke production is highly dependent on milk production and quality. The farmer's problems are low production and quality of Holstein Friesian milk, high production costs, expensive concentrate, and the farmers holding limited arable pastures that are not high enough to provide feed for cows. Chemical fertilizer input is one way to increase the dry matter (DM) yield of forage. However, the prices are increasing by more than 100%. Thus, the objective of this program is to implement the alley cropping system to increase DM yield and pasture quality. The program begins with socialization, sharing knowledge, and discussion with the farmers, and the next day continues with transplanting Indigofera zollingeriana to Pennisetum purpureum pasture for arranging the alley cropping system. Implementing this system not only increases the DM yield and forage quality but also reduces fertilizer costs. High DM yield and pasture quality will provide pasture to meet the target of increasing milk production and quality. The increase in milk production and quality will increase Dangke production, it leads increasing the farmers' life. Keywords: alley cropping system, dangke, Indigofera